2017
DOI: 10.1002/jum.14414
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Evaluating Achilles Tendon Vascularization Assessed With Doppler Ultrasound Advanced Dynamic Flow

Abstract: Objectives The reliability of quantifying intratendinous vascularization by high‐sensitivity Doppler ultrasound advanced dynamic flow has not been examined yet. Therefore, this study aimed to investigate the intraobserver and interobserver reliability of evaluating Achilles tendon vascularization by advanced dynamic flow using established scoring systems. Methods Three investigators evaluated vascularization in 67 recordings in a test‐retest design, applying the Ohberg score, a modified Ohberg score, and a cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…We found good interobserver reliability for the SAQ method (ICC, 0.81) compared to moderate interobserver reliability for the modified Öhberg score (ICC, 0.64). Similar findings for the ICC of the modified Öhberg score were published by Risch et al, in which moderate absolute interobserver agreement (0.64–0.80) was also observed. Sengkerij et al and Watson et al observed considerably higher ICCs for the modified Öhberg score (0.85 and 0.86, respectively).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…We found good interobserver reliability for the SAQ method (ICC, 0.81) compared to moderate interobserver reliability for the modified Öhberg score (ICC, 0.64). Similar findings for the ICC of the modified Öhberg score were published by Risch et al, in which moderate absolute interobserver agreement (0.64–0.80) was also observed. Sengkerij et al and Watson et al observed considerably higher ICCs for the modified Öhberg score (0.85 and 0.86, respectively).…”
Section: Discussionmentioning
confidence: 90%
“…Second, we have not determined intraobserver reliability. In patellar tendinopathy, it was previously demonstrated that day‐to‐day variability in Doppler flow is present; however, in midportion AT, it was shown that the intraobserver reliability of the modified Öhberg score was excellent . Future research should investigate the intraobserver reliability of the SAQ method to verify the diagnostic value of SAQ.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations